Exploring IT Students’ Use of Generative AI for Technical Vocabulary Learning: A Qualitative Study - Ninh Nguyen Tuan (An-Nasyi'in: Jurnal Ilmu Pendidikan, 2026)
This study explores how Information Technology (IT) students use generative Artificial Intelligence (AI) tools to support technical vocabulary learning in an English for Specific Purposes (ESP) context. Adopting a qualitative design, the study involved 20 third-year IT students at a private university in Hanoi, Vietnam. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings indicate that students use generative AI as part of a multimodal learning ecosystem, combining tools such as chatbots and coding assistants to explain technical terms, generate examples, and simplify complex concepts. AI was found to enhance conceptual understanding and promote learner autonomy. However, concerns regarding over-reliance and the accuracy of AI-generated content were also reported. The study highlights the importance of guided AI integration and the development of critical AI literacy in ESP instruction.